Vocal foragers and silent crowds: context-dependent vocal variation in Northeast Atlantic long-finned pilot whales - Visser, Fleur; Pierce, Graham J.; Miller, Patrick J. O. (Behavioral Ecology and Sociobiology, 2017)
13 pages, 6 figures, 3 tables.-- Fleur Visser . et al.-- This article is an open access publication Vocalisations form a key component of the social interactions and foraging behaviour of toothed whales. We investigated changes in calling and echolocation behaviour of long-finned pilot whales between foraging and non-foraging periods, by combining acoustic recordings and diving depth data from tagged individuals with concurrent surface observations on social behaviour of their group. The pilot whales showed marked vocal variation, specific to foraging and social context. During periods of foraging, pilot whales showed more vocal activity than during non-foraging periods (rest, travel). In addition to the expected increase in echolocation activity, call rates also increased, suggesting that pilot whales communicate more during foraging. Furthermore, calls with multiple inflections occurred more often immediately before and after foraging dives and during the early descent and late ascent phases of foraging dives. However, these calls were almost never detected at diving depths of the tagged whale beyond 350 m. Calls with no or few inflections were produced at all times, irrespective of diving depth of the tagged whale. We discuss possible explanations for the distinct vocal variation associated with foraging periods. In addition, during non-foraging periods, the pilot whales were found to be more silent (no calling or echolocation) in larger, more closely spaced groups. This indicates that increased levels of social cohesion may release the need to stay in touch acoustically. This study was financially supported by the US Office of Naval Research, The Netherlands Ministry of Defence, the Norwegian Research Council and the Norwegian Ministry of Defence Peer reviewed